An Investigation into the Shift of Joint Ventures to Wholly Owned Subsidiaries in China - Wang, Kun (2009)
The following study seeks to identify the possible reasons why Joint Venture will gradually become wholly owned subsidiaries in China. To identify and research a framework and arrive at a proper conclusion for the research, this dissertation reviews various theories of FDI, theories of entry mode, and so on. The research method of this dissertation is a case study. There are two cases - P&G and Panasonic which have been discussed to address the reasons why there is such a change in tendency among foreign investment companies in China.